2022
DOI: 10.1038/s43586-022-00104-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanodelivery of nucleic acids

Abstract: Gene therapy uses nucleic acids as functional molecules to activate biological treatment for a wide range of diseases, such as cancer 1,2 , cystic fibrosis 3 , heart disease 4 , diabetes 5 , haemophilia and HIV/AIDS 6 . Nucleic acids have been attracting increasing attention owing to the global effort in the human genome elucidation together with recent discoveries such as RNA interference (RNAi) and CRISPR-based genome editing [7][8][9] . Gene therapy uses genetic material to alter the expression of a target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
206
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(207 citation statements)
references
References 231 publications
0
206
0
1
Order By: Relevance
“…In recent times, microfluidic mixing approaches were designed based on rapid-mixing approach which further promises to fabricate nucleic acid, and protein loaded LNPs in a more reproducible and scalable fashion. It was further observed that all the mentioned methods allow rapid mixing of lipid containing organic phase into aqueous phase comprised of nucleic acid, and proteins, and resulting in an enhanced entrapment efficiency [ 38 ].…”
Section: Lipid-based Nanoparticles: a Versatile Drug Delivery Systemmentioning
confidence: 99%
“…In recent times, microfluidic mixing approaches were designed based on rapid-mixing approach which further promises to fabricate nucleic acid, and protein loaded LNPs in a more reproducible and scalable fashion. It was further observed that all the mentioned methods allow rapid mixing of lipid containing organic phase into aqueous phase comprised of nucleic acid, and proteins, and resulting in an enhanced entrapment efficiency [ 38 ].…”
Section: Lipid-based Nanoparticles: a Versatile Drug Delivery Systemmentioning
confidence: 99%
“…This step aspires to the design of nanocarriers in a way to promote anti-cancer/nucleic acid endosomal escape. More details concerning nucleic acid endosomal escape were better highlighted and investigated by Mendes et al ( Mendes et al, 2022 ).…”
Section: Required Nanotherapeutics Properties For An Efficient Deliverymentioning
confidence: 99%
“…Within the past decade, the molecular understanding of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) biomolecules in controlling cellular physiology has gathered excitement in the field to commercialize a wide variety of products such as antisense oligonucleotides, non-coding microRNAs (miRNAs), short interfering RNA (siRNA), and messenger RNA (mRNA). 337 With the latter showing exuberant interest internationally with Pfizer and BioNTech, and Moderna Therapeutics in creating the mRNA-based vaccines for COVID-19; 338,339 however, the long-term efficacy, safety, and immunogenicity remains to be understood under long-term surveillance. One of the approaches for biomaterials/gene editing is the encapsulation of diverse genome editing cargoes.…”
Section: Gene Editing Biomaterials For the Management Of Retinoblastomamentioning
confidence: 99%